Close to Death : a novel - Horowitz, Anthony, 1955- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2024)
"In New York Times bestselling author Anthony Horowitz's new and ingenious literary whodunnit, Detective Hawthorne is once again called upon to solve an unsolvable case--a gruesome murder in an idyllic gated community in which suspects abound"--Dust jacket flap
"Riverside Close is a picture-perfect community. The six exclusive and attractive houses are tucked far away from the noise and grime of city life, allowing the residents to enjoy beautiful gardens, pleasant birdsong, and tranquility from behind the security of a locked gate. It is the perfect idyll, until the Kentworthy family arrives, with their four giant, gas-guzzling cars, gaggle of shrieking children, and plans for a garish swimming pool in the backyard. Obvious outsiders, the Kentworthys do not belong in Riverside Close, and quickly offend every last one of the neighbors. When Giles Kentworthy is found dead on his own doorstep, a crossbow bolt sticking out of his chest, Detective Hawthorne is the only investigator they can call to solve the case. Because how do you solve a murder when everyone is a suspect?"--
Keywords: Horowitz, Anthony, -- 1955- -- Fiction; Hawthorne, Daniel -- (Fictitious character) -- Fiction; Murder -- Fiction; Murder -- Investigation -- Fiction; Private investigators -- Fiction; Authors -- Fiction; Gated communities -- Fiction; Neighbors -- Fiction; Homicide -- Fiction; Neighbors -- Fiction; Private investigators -- Fiction; Authors -- Fiction; England -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Novels; Romans